A simple efficient GMM estimator of GARCH models - Jimmy Skoglund (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
This paper is concerned with efficient GMM estimation and inference in GARCH models. Sufficient conditions for the estimator to be consistent and asymptotically normal are established for the GARCH(1,1) conditional variance process. In addition efficiency results are obtained in the general framework of the GARCH(1,1)-M regression model.
Keywords: C12; C13; C22; 330; GARCH; GARCH-M; efficient GMM; ARCH-Modell; Schätztheorie; Theorie